Conodont biostratigraphy of a Carboniferous–Permian boundary section in siliceous successions of pelagic Panthalassa revealed by X-ray computed microtomography - Muto, Shun; Takahashi, Satoshi; Murayama, Masafumi (Frontiers in Earth Science, 2023)
Pelagic deep-sea siliceous successions in accretionary complexes preserve precious records of a vast deep seafloor that is now lost due to plate subduction. Microfossils are the key means of age assignment of these successions, but poor preservation due to tectonic deformation and metamorphism at the subduction zone hamper biostratigraphic records. X-ray computed microtomography, while not widely used in biostratigraphic studies until now, allows us to visualize fossils that are impossible or difficult to extract from host rocks due to poor preservation. In this study, we applied this method on conodonts from a pelagic chert–claystone succession in Okoshizawa, Iwaizumi Town, Northeast Japan, using a laboratory-based X-ray microscope. This work is a first close look at conodont biostratigraphy across the Carboniferous–Permian boundary in pelagic deep Panthalassa. We identified conodonts including ten species that are used as zonal markers in intensely studied areas such as around the East European Platform and Midcontinent USA. Based on the occurrence of conodonts, the studied section in Okoshizawa was correlated to the lower Moscovian to middle Artinskian. Confirmation of Moscovian to Artinskian age diagnostic conodonts from pelagic Panthalassa strengthens their role as global biostratigraphic indicators. By identifying more numerous specimens compared to the conventional HF acid dissolution method, we were able to obtain information about conodont faunal characteristics around the Carboniferous–Permian boundary in pelagic deep areas of Panthalassa. The dominant taxa changed from Streptognathodus to Mesogondolella in the middle Asselian, probably reflecting an ecological takeover by the latter in the deep waters.